Home and away: hybrid perspective on identity formation in 1.5 and second generation adolescent immigrants in Israel (Glocalism: Journal of Culture, Politics and Innovation, 2013)
Immigration is not only about changing countries, but also about shifting identities. This change is especially important for adolescents. This article examines identity formation among 1.5 and 2nd generation adolescent immigrants to Israel. A survey of 125 children of immigrants aged 12-19 examined the role of social structures such as pace of life, culture, religion and language on identity formation in 1.5 and 2nd generational groups. We have identified several significant factors affecting the identities of children of migrants in each group. Looking beyond self-labeling, we argue that identity formation among children of immigrants is a continuous process in which the host country and origin country, both or neither of them, create dynamic hybrid patterns of identifications.
Keywords: hybridity; immigration; Israel; identity; generational groups